Evaluation of Urinary Catheters Coated with Sustained‐Release Varnish of Chlorhexidine in Mitigating Biofilm Formation on Urinary Catheters in Dogs. (9th November 2012) - Segev, G.; Bankirer, T.; Steinberg, D.; Duvdevani, M.; Shapur, N.K.; Friedman, M.; Lavy, E.
<x xml:space="preserve">Abstract</x> Background Biofilm formation occurs commonly on urinary catheters. Objectives To assess the efficacy of urinary catheters coated with sustained‐release varnish of chlorhexidine in decreasing catheter‐associated biofilm formation in dogs. Animals Thirty client‐owned dogs. Methods Prospective study. Thirteen dogs were catheterized with urinary catheters coated with sustained‐release varnish of chlorhexidine (study group), and 13 dogs were catheterized with an untreated urinary catheter (control group). Presence and intensity of biofilm formation on the urinary catheters were assessed and compared between the groups by evaluating colony‐forming units (CFU) of biofilm bacteria, and semiquantitatively, using confocal laser scanning microscopy and electron microscopy. Results None of the dogs experienced adverse effects associated with the presence of the urinary catheters. Median CFU count of biofilm bacteria at all portions of the urinary catheter was significantly (P < .001) lower in the study compared with the control group. The degree of biofilm formation on the urinary catheters, as evaluated by confocal laser scanning microscopy and electron microscopy, was significantly lower in the study compared with the control group. Electron microscopy examination identified crystals on some of the urinary catheters. The proportion of catheters on which crystals were observed was significantly lower on the distal part of the urinary catheter in the study group compared with the control group (16.7% versus 66.7%, respectively; P = .04). Conclusions and Clinical Importance Chlorhexidine sustained‐release varnish‐coated urinary catheters effectively decrease urinary catheter‐associated biofilm formation in dogs.